2021
DOI: 10.3390/brainsci11060739
|View full text |Cite
|
Sign up to set email alerts
|

Transient Modulation of Working Memory Performance and Event-Related Potentials by Transcranial Static Magnetic Field Stimulation over the Dorsolateral Prefrontal Cortex

Abstract: Transcranial static magnetic field stimulation (tSMS) can modulate human cortical excitability and behavior. To better understand the neuromodulatory effect of tSMS, this study investigates whether tSMS applied over the left dorsolateral prefrontal cortex (DLPFC) modulates working memory (WM) performance and its associated event-related potentials (ERPs). Thirteen healthy participants received tSMS or sham stimulation over the left DLPFC for 26 min on different days. The participants performed a 2-back version… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…For example, Watanabe et al (2021) observed that applying tSMS for 30 minutes over the left DLPFC did not affect performance in a Go/noGO task (Watanabe et al, 2021). On the other hand, tSMS over the left DLPFC decreased performance in a working memory n-back task without affecting the reaction times (Chen et al, 2021). With respect to the RNG task, random number generation in human subjects can be accompanied by lateral head turns and eye position (Loetscher et al, 2010(Loetscher et al, , 2008.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Watanabe et al (2021) observed that applying tSMS for 30 minutes over the left DLPFC did not affect performance in a Go/noGO task (Watanabe et al, 2021). On the other hand, tSMS over the left DLPFC decreased performance in a working memory n-back task without affecting the reaction times (Chen et al, 2021). With respect to the RNG task, random number generation in human subjects can be accompanied by lateral head turns and eye position (Loetscher et al, 2010(Loetscher et al, , 2008.…”
Section: Discussionmentioning
confidence: 99%
“…The kind of stimulation was blinded to the participants and experimenters. To avoid carryover effects (Carrasco-López et al, 2017;Chen et al, 2021;Gonzalez-Rosa et al, 2015;Oliviero et al, 2011;Sheffield et al, 2019;Vila-Villar et al, 2022), each of these stimulations was performed in two sessions on different days (at least one week apart) using the same protocol. The performance of the second RNG is unaffected by repeated performance or practice (Jahanshahi et al, 2006).…”
Section: Experimental Designmentioning
confidence: 99%
“…The visual stimuli were displayed for 500 ms with an interstimulus interval of 1,000–1,300 ms. (C) In Experiment 1, a magnet and a non-magnetic stainless-steel cylinder (sham) were placed on the MAC using the custom headgear. This image is adapted from a previous study under Creative Commons Attribution (CC BY) license ( Chen et al, 2021 ). (D) In Experiment 2, triple tSMS (or sham) was held using an arm type lighting stand.…”
Section: Methodsmentioning
confidence: 99%
“…In comparison to the other NIBS expected to induce inhibitory effects, such as cathodal transcranial direct current stimulation (tDCS) ( Nitsche and Paulus, 2000 ), low-frequency repetitive transcranial magnetic stimulation (LF-rTMS) ( Chen et al, 1997 ), continuous theta-burst stimulation (cTBS) ( Huang et al, 2005 ), which induce electric current flow, tSMS (that induces SMF) causes less discomfort to the participants and is safe, economical, and easy to handle. In the past decade, various local brain regions such as the sensorimotor ( Silbert et al, 2013 ; Kirimoto et al, 2014 , 2016 , 2018 ; Nojima et al, 2015 , 2019 ; Davila-Perez et al, 2019 ; Nakagawa et al, 2019 ; Shibata et al, 2020 ), supplementary motor ( Kirimoto et al, 2016 ; Pineda-Pardo et al, 2019 ; Tsuru et al, 2020 ; Guida et al, 2023 ), visual ( Gonzalez-Rosa et al, 2015 ; Oliviero et al, 2015 ; Lozano-Soto et al, 2018 ), and dorsolateral prefrontal ( Sheffield et al, 2019 ; Chen et al, 2021 ; Watanabe et al, 2021 , 2023 ; Soto-León et al, 2023 ) cortices have been revealed to be modulated by tSMS, with potential clinical applications for neurological disorders ( Di Lazzaro et al, 2021 ; Dileone et al, 2022 ; Shimomura et al, 2023 ). In addition, a new tSMS device constructed with three NdFeB magnets (called “SHIN jiba”) was introduced last year, and simulation has revealed that this triple tSMS can produce the greater static magnetic fields than the conventional tSMS ( Shibata et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation